Invisible - Auster, Paul, 1947- (New York : Henry Holt and Co., 2009)
Poet and student Adam Walker meets the enigmatic Frenchman Rudolf Born and his silent, seductive girlfriend, Margot, sending Adam into a perverse triangle that leads to a shocking act of violence that will alter his life.
'A Frances Coady book.'
Keywords: College students -- Fiction; Poets -- Fiction; Nineteen sixties -- Fiction; Triangles (Interpersonal relations) -- Fiction; Psychological fiction